COMPARATIVE ANALYSIS OF GREEN TECHNOLOGY INVESTMENTS IN MEGA-REGIONS: THE CASES OF THE UNITED STATES, EUROPE, AND PEOPLE’S REPUBLIC OF CHINA (INNOVATIVE ECONOMY, 2025)
Chukhnii O.Yu., Lutsiv R.S.  COMPARATIVE ANALYSIS OF GREEN TECHNOLOGY INVESTMENTS IN MEGA-REGIONS: THE CASES OF THE UNITED STATES, EUROPE, AND PEOPLE’S REPUBLIC OF CHINA Purpose. This article aims to provide a comparative analysis of green technology investments across prominent mega-regions in the United States, Europe, and China by examining the scale, sectoral focus, and underlying drivers of these investments, highlighting the similarities and differences in their approaches to fostering a more sustainable urban future.Methodology of research. General scientific and specialized methods were used during the study. Inductive and deductive reasoning guided the collection and processing of data. The comparative method enabled analysis of the scale, structure, and dynamics of green technology investments in major mega-regions of the U.S., Europe and China. Content analysis was used to examine strategic documents and reports, while statistical analysis assessed indicators such as investment volumes and public and private funding ratios. Case studies of key regions (e.g., Greater Bay Area, Northeastern Corridor, and Blue Banana) offered deeper insights. A systematic literature review synthesized existing research on green transitions and sustainable urban development.Findings. It has been established that investments in green technologies in the United States, Europe, and China share common strategic priorities, particularly the development of renewable energy, electric transport, and sustainable urban environments. It has been substantiated that key differences lie in the scale of investment, institutional structures, and governance mechanisms: China demonstrates a centralized model, the U.S. a decentralized one, and the EU relies on multi-level coordination through European Union policy.It has been proven that China currently leads in terms of funding volume, driven by national priorities for “green” economic growth and strict state regulation. The analysis shows that the U.S. is dominated by a market model focused on private investment, state-level initiatives, and technological innovation, whereas Europe aims for global leadership through coordinated environmental policies and financial instruments.It has been identified that public support and institutional interaction remain decisive success factors, although their influence varies significantly across the three regions. The comparative analysis has made it possible to highlight shared sustainable development goals, which create favourable conditions for strengthening international cooperation and exchanging effective practices, despite differing approaches to political governance (fragmented in the U.S., multi-level in the EU, and centralized in China).Originality. For the first time, an integrative approach has been substantiated for analysing investments in green technologies across major global mega-regions (the USA, the EU, and China). Unlike existing studies, which are mostly focused on individual countries or sectors, this approach enables a systematic comparison of investment strategies, political frameworks, and structural features of ecological modernization.It has been proven that the effectiveness of investments in green technologies is largely determined by the type of political governance – fragmented (USA), multi-level (EU), and centralized (China) – which significantly influences the scale, pace, and institutional stability of the green transition.It has been established that shared sustainable development goals, despite differing approaches, create synergistic opportunities for international cooperation, exchange of best practices, and the formation of global environmental partnerships.Methodological approaches to the comparative analysis of green investments have been improved through the development of an interregional analytical model that links investment dynamics with sustainable urban development outcomes.Scientific understanding of the role of institutional factors – particularly innovation ecosystems, environmental legislation, and state support – in shaping investment flows in the green technology sector has been further advanced.The proposed approach offers deeper insight into the interconnection between environmental policy, urban transformations, and global economic trends.Practical value. This research provides valuable insights for policymakers, urban planners, and investors by identifying key drivers, challenges, and best practices in green technology across major mega-regions. It supports targeted investment strategies, fosters regional cooperation, and promotes model replication. The article examines targeted investment strategies and analytical tools that can be used to support regional cooperation and scale up effective models. The proposed analytical framework enables the assessment of innovation potential and guides the development of sustainable urban environments.Key words: mega-regions, urban archipelagos, green technologies investments, sustainable economic growth, renewable energy, global economic environment, funding mechanisms.
Keywords: mega-regions; urban archipelagos; green technologies investments; sustainable economic growth; renewable energy; global economic environment; funding mechanisms